The Effectiveness of Warm Water Foot Soak Therapy and Rose Aroma Therapy on Lowering Blood Pressure and Anxiety in Hypertensive Patients : Literature Review - Muhith, Abdul; Subairi, Moh; Mampesi, Anastasa; Oliveira, Adirson Barbosa de; Zulkarnain, Eva Vera; Mahyuvi, Tata; Fatkan, Moch; Muthoharoh, Anies (Journal of Applied Nursing and Health, 2024)
Background: Hypertension is a disease that can cause anxiety for sufferers, this is because the disease is the main factor in the occurrence of other diseases such as stroke, this must be treated immediately by doing a combination of non-pharmacological and pharmacological treatment to reduce symptoms and complications that may occur. The purpose  of this literature review is to determine the effectiveness of warm water foot soak therapy and the administration of rose aroma therapy on reducing blood pressure and anxiety in hypertensive patients Methods: The method used PRISMA Approach for this article is literature review using a journal database  from Google Scholar in the period of  2018-2023 with search keywords namely "soak the feet of warm water of hypertensive patients", and "aroma therapy rose with anxiety" to find relevant articles found as many as 3,250 articles from Google Scholar). Results: Articles were selected according to the criteria and obtained the results of 10 articles that were ready to be reviewed. The results of this study showed that it was proven effective in soaking warm water feet and giving rose aroma therapy to reduce blood pressure and anxiety in hypertensive patients. Conclusion: The conclusion of the 10 articles reviewed, showed that thefire of soaking the feet of warm water and giving rose aroma therapy showed a positive response in lowering blood pressure and anxiety